CAUSES AND EFFECTS OF EXAMINATION MALPRACTICE ON ACADEMIC PERFORMANCE OF SENIOR SECONDARY SCHOOL STUDENTS IN MAIDUGURI METROPOLIS, BORNO STATE - Aliyu, Gambo Mustapha; Askira, Ibrahim Mohammed; Umar, Saleh (Sokoto Educational Review, 2017)
The study examined the causes of examination malpractice and its effects on the academic performance of senior secondary school students in Maiduguri Metropolis, Borno State. Three objectives were stated and three research questions were answered. The study used a survey research design. The population of the study was the entire government secondary school students in Maiduguri Metropolis. A simple random sampling technique was used to select three (3) out of the seventeen (17) secondary schools as the sample for the study. A simple random sampling technique was also used to obtain a sample of 50 SS II and SS III students from each of the three selected secondary schools. That is 50 students from each school, making a total of 150 students. The instrument used was a structured questionnaire, which was designed by the researchers. The questionnaire was personally administered ed by the researchers during the regular lesson period and was collected on the spot after completion by the respondents. The data obtained were analyzed using frequency count and percentage scores. The findings of the study revealed that inadequate teaching, poor supervision, moral decadence, and teachers’ involvement are some of the causes of examination malpractice. The study also showed that a decline in the standard of education is one of the most serious consequences of examination malpractice. The study recommended that teachers should engage in proper classroom teaching, Government should employ qualified teachers and provide enough teaching facilities, school and examination bodies should take all necessary measures to ensure that examination malpractice is minimized among others.